Systemic inflammatory immune signatures in a patient with CRB1 linked retinal dystrophy. (1st December 2016) - Verhagen, Fleurieke; Kuiper, Jonas; Nierkens, Stefan; Imhof, Saskia M.; Radstake, Timothy; de Boer, Joke
ABSTRACT: Background : In this report we describe, for the first time, the activation of the peripheral immune compartment in a patient with a CRB1 linked retinal degenerative disease, masquerading as intermediate uveitis. Methods : To monitor the immune system during systemic immunosuppressive treatment, given for the initial diagnosis of intermediate uveitis, blood samples were taken before and during therapy, for analysis of peripheral blood mononuclear cell-subsets and circulating immune mediators. Results : The levels of various pro-inflammatory immune mediators (including MIF, TSLP, CCL2/MCP-1, CXCL9, CXCL10, IFN-β, IL-6, IL-17, IL-21, IL-22, and IL-23) were elevated in serum at the first time point, and decreased under immunosuppressive treatment. In parallel, the frequency of activated (CD86+) CD1c+ myeloid dendritic cells in blood was proportional to the central foveal thickness measured by optical coherence tomography. Conclusions : These observations challenge the current view on the distinct pathophysiology of retinal degenerative and retinal inflammatory conditions in this patient.